A light weight encryption over big data in information stockpiling on cloud - Uma Narayanan; Varghese Paul; Shelbi Joseph (Institute of Advanced Engineering and Science, 2020)
Data is growing exponentially in the fast Changing World of Information and Communications Technology. Information from sensors, cell phones, social networking sites, logical information and ventures all are adding to this gigantic blast in the information. One of the best mainstream utilities available for dealing with the colossal measure of data is the Hadoop community. Enterprises are progressively depending on Hadoop for preparing their essential information. In any case, Hadoop is still developing. There is much powerlessness found in Hadoop, which can scrutinize the security of the sensitive data that undertakings have entrusted on it. In this paper, security issues related to the system have been discussed. Besides, we have attempted to give a short overview of the currently accessible arrangements and their constraints. Towards the end, a novel strategy, which can be utilized to kill the detected vulnerabilities in the structure, has been introduced. In the cutting edge period, data security has moved towards becoming a basic need for every single person. Be that as it may, not every person can bear the cost of the specific circulations given by various sellers to their Hadoop group. This paper displays an effective system that anybody can use with their Hadoop to secure Data.